Pengaruh Kompaksi dan Kandungan Grafit Terhadap Karakteristik Mekanis Bantalan Luncur Connecting Rod - Ali Medi; Djoko W Karmiadji (Forum Teknik, 2010)
AbstractBearing is an important component in the automotive industry that is needed to be made of material having good properties. Aluminum graphite matrix composite becomes a selected tribology application in self-lubricating bearing. This composite has good wear resistance andlow density compared with bronze bearing material so that gives more economical values. This research is done by the method of powder metallurgy with aluminum matrix composite material using an additive of 5% graphite weight fraction. Variable compactions (P) are 400 MPa, 500MPa, 600 MPa and sintering temperature is 5500C, with variable holding times (HT) 1 hour, 2 hours and 3 hours. The study aims to analyze the effect of graphite content affecting the mechanical properties of aluminum graphite composite material. The test results show that the optimum condition of 5% graphite content is the density = 5.11 gr/cm3, the hardness = 54.449 HB, the compressive strength = 790 MPa, when P = 600 MPa and HT = 3 hours.Keywords: aluminium, komposit, serbuk, kompaksi, holding time.